2016
DOI: 10.5194/hess-20-4757-2016
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting transit times of water from peatlands and eucalypt forests in the Australian Alps determined by tritium: implications for vulnerability and the source of water in upland catchments

Abstract: Peatlands are a distinctive and important component of many upland regions that commonly contain distinctive flora and fauna which are different from those of adjacent forests and grasslands. Peatlands also represent a significant long-term store of organic carbon. While their environmental importance has long since been recognised, water transit times within peatlands are not well understood. This study uses tritium ( 3 H) to estimate the mean transit times of water from peatlands and from adjacent gullies th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 54 publications
1
23
0
Order By: Relevance
“…Groundwater age is an extremely important indicator of the groundwater replenishment (Bethke & Johnson, ; Cresswell et al., ; Jasechko, ). Tritium ( 3 H), a radioactive isotope of hydrogen with a concentration that spiked in precipitation approximately 50 years ago as a result of aboveground thermonuclear testing, is commonly applied in hydrologic cycle research to determine whether modern water supplies exist (Cartwright & Morgenstern, ; Egboka et al., ; Morgenstern et al., ; Robertson & Cherry, ; Solomon et al., ; Young et al., ). Many studies have shown that water with 3 H contents of <1 TU is regarded as having a pre‐1952 age (Farid et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Groundwater age is an extremely important indicator of the groundwater replenishment (Bethke & Johnson, ; Cresswell et al., ; Jasechko, ). Tritium ( 3 H), a radioactive isotope of hydrogen with a concentration that spiked in precipitation approximately 50 years ago as a result of aboveground thermonuclear testing, is commonly applied in hydrologic cycle research to determine whether modern water supplies exist (Cartwright & Morgenstern, ; Egboka et al., ; Morgenstern et al., ; Robertson & Cherry, ; Solomon et al., ; Young et al., ). Many studies have shown that water with 3 H contents of <1 TU is regarded as having a pre‐1952 age (Farid et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, quantifying groundwater age by radioisotopes to trace groundwater migration pathways is also effective for identifying regional water cycles through isotopic methods (Bethke & Johnson, ; Cartwright, Cendon, Currell, & Meredith, ; Clark & Fritz, ; Cresswell, Jacobson, Wischusen, & Fifield, ; Hagedorn, ; Kalin, ). For example, tritium ( 3 H), a radioactive isotope of hydrogen with a concentration that spiked in precipitation approximately 50 years ago as a result of aboveground thermonuclear testing, is commonly applied in hydrologic cycle research to determine whether modern water supplies exist (Cartwright & Morgenstern, ; Egboka, Cherry, Farvolden, & Frind, ; Morgenstern, Stewart, & Stenger, ; Robertson & Cherry, ; Solomon, Poreda, Cook, & Hunt, ; Young, Broughton, Bradd, & Holland, ).…”
Section: Introductionmentioning
confidence: 99%
“…It can therefore be concluded that EC was the only environmental tracer that provided results consistent with those of the pumping well dynamics method for the three different drawdowns. However, results calculated by using TDS and temperature as tracers were not as consistent with the pumping well dynamics method as EC due to the applicability of different parameters and the impact of the uncertainty (Cartwright & Morgenstern, ). Therefore, in the study area, EC can be effectively used as environmental tracers to ascertain the mixing ratio between the river water and the groundwater.…”
Section: Discussionmentioning
confidence: 99%
“…We tested six TTDs commonly applied in hydrologic systems: the exponential, linear, exponential‐piston flow (EPF), linear‐piston flow (LPF), advection–dispersion (AD, Maloszewski & Zuber, ; Cook & Böhlke, ), and the gamma model (Kirchner, Feng, & Neal, ). Although the EPF and AD models have been used in riverbank infiltration studies (e.g., Kármán, Maloszewski, Deák, Fórizs, & Szabó, ; Maloszewski, Rauert, Trimborn, Herrmann, & Rau, ; Stichler et al, ; Stichler et al, ) and in groundwater studies (e.g., Cartwright & Morgenstern, ; M. K. Stewart, Morgenstern, Gusyev, & Małoszewski, ), the exponential and gamma models have been widely applied for catchment mTT modelling (cf. K. J. McGuire & McDonnell, ; Hrachowitz et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…To improve the convergence of Monte Carlo simulations, we limited P D to 1 (cf. Cartwright & Morgenstern, ), which is appropriate for kilometre‐scale flow systems (Mook & Rozanski, ). The range of the shape parameter ( α ) in the gamma model was limited to 10, following Timbe et al () and M. K. Stewart et al ().…”
Section: Methodsmentioning
confidence: 99%